Metabolite Profiling of 96% Ethanol Extract from Marsilea crenata Presl. Leaves Using UPLC-QToF-MS/MS and Anti-Neuroinflammatory Predicition Activity with Molecular Docking - Burhan Ma’arif; Denis; Arief Suryadinata; Artabah; Hening Laswati; Mangestuti Agil (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
Phytoestrogen is a group of compounds that can replace the estrogen function in the body. One of its roles was as anti-neuroinflammatory by inhibiting the microglia M1 polarity activation. Marsilea crenata Presl. is a plant that suspected to contain phytoestrogens. The aim of this research was to determine the metabolite profile of 96% ethanol extract of M. crenata using UPLC-QToF-MS/MS, and prediction the anti-neuroinflammatory activity of compounds with molecular docking. The 100 ppm of 96% ethanol extract in DCM and methanol were injected 5 µl each into the UPLC-QToF-MS/MS, and then analyzed by Masslynx 4.1 software to determine the compounds. The result of metabolite profiling shows a total 59 compounds in both DCM and methanol. Molecular docking was done with Autodock 4.2.6. After being analyzed, there are 3 compounds that are predicted to have activities similar to 17?-estradiol, they are prochlorperazine, 12-Aminododecanoic acid, and 1-methyl-2-[(4-methylpiperazin-1-yl)methyl]benzimidaol-5-amine hydrochloride. The results showed that the three compounds were predicted to be phytoestrogen compounds from M. crenata leaves, which have potential as anti-neuroinflammatory.